NFB-02. TREATMENT OF PAIN AND TUMOR GROWTH IN NF2. (4th December 2020) - Hemenway, Molly; Nellan, Anan; McMahon, Kate; Foreman, Nicholas; Reddy, Kartik; Nellan, Anan; Suttman, Alexandra
Abstract: BACKGROUND: Neurofibromatosis Type 2 (NF2) is an autosomal dominant disorder characterized by multiple nervous system tumors. Chronic pain affects the majority of patients with NF2 and is the primary factor that contributes to decreased quality of life. There are limited therapies that effectively reduce pain in NF2, but intravenous (IV) bevacizumab has been reported to provide significant relief to patients suffering from debilitating pain. CASE STUDY: James is a 24-year-old who initially presented with manifestations of NF2 at age 10, and by 15 years old had developed daily pain affecting his neck, back, and lower extremity. He has multiple CNS schwannomas, meningiomas, neurofibromas, and meets clinical NF2 criteria. While genetic testing did not reveal a mutation in his gDNA, low level skipping of exon 4 via RNA supports (likely mosaic) NF2. James's pain was poorly controlled with multiple oral medications, including opioids. James started IV bevacizumab at age 16 that improved his pain. He was critically dependent on bevacizumab for pain control and required continuous IV pain medication when bevacizumab was held for a surgical procedure. Following five years of bevacizumab he developed worsening toxicities including hypertension, proteinuria, and elevated hemoglobin. James transitioned to therapy with trametinib, a MEK inhibitor, and was able to wean off bevacizumab six months later. Treatment of NF2 related pain with trametinib instead of bevacizumab has improved his QOL with decreased medical visits, improved pain management, and decreased side effects. FUTURE IMPLICATIONS: Treatment of NF2 tumor related pain can be managed with MEK inhibitors.